PENGAWASAN DINAS PERTAMBANGAN DAN ENERGI KABUPATEN LANDAK DALAM KEGIATAN PERTAMBANGAN EMAS TANPA IZIN DI KECAMATAN NGABANG - Merry Antasari E.01109049 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Illegal golg mining is rife in the District Ngabang because this region has a great potential to be a gold mining materials. Mining is carried out by the miners not only to meet the needs of everyday life, but has led to efforts to enrich themselves. Therefore, the mining is done no longer pay attention to their health and safety. Excessive mercury substance use and environmental damage resulting mined these activities are not allowed by the authorities. Supervision is one of the efforts taken by the Department of Mines and Energy District Landak to stop illegal gold mining in the district Ngabang. The method used in this paper the qualitative method. That is, in this study the data were not collected in the form of numbers, but the data derived from the interview process, the researcher notes, documentation researchers and official documents of the department concerned. In the writing of this article can be seen that the surveillance conducted by the department have not been effective due to the large costs required and the socialization of the dangers of mercury was not effective. Therefore, through this study is expected that the Department of Mines and Energy District Landak can increase surveillance activities. Keywords: Illegal Gold Mining, Supervision of Mines.